Role of Extracted Nano-metal Oxides From Factory Wastes In Medical Applications - Ghdeeb, Nadia Jasim; AbdulMajeed, Aseel Mustafa; Mohammed, Asma Hadi (Iraqi Journal of Science, 2023)
Nanometal oxides were extracted from cement factories wastes and were employed to proliferate skin cancer cells using MTT (Methyl Thiazolyl Tetraolium) assay. MTT assay results for skin cancer cell line A375,for CaO NPs the best concentration was 200 μg/mL,The viability was reduced to 57.28% while the IC50 was (69.66) g/mL for A375 and normal cell WRL68 was significantly higher (231.2 g/mL). The cytotoxicity results of CaO: MgO: Fe2O3 NPs, at higher concentrations (200 and 400) μg/mL showed a significant difference. The IC50 was (106.4) μg/mL for A375and normal cell WRL68 was significantly higher (173.3) μg/ml CaO:MgO:Fe2O3 NPs. The nanometal oxides, calcium oxide (CaO) and the mixture (CaO:MgO: Fe2O3) were extracted from wastes of cement factory, and then they were oxidized at a temperature of 400C° for (5) hours. The structural and surface properties of the prepared oxides were characterized by X-ray diffraction patterns,FE-SEM and FTIR. The X-ray data reflected that all the oxides have a polycrystalline cubic structure, with a preferred orientation along (111) for calcium oxide, with a preferred orientation along (002) for calcium oxide: magnesium oxide: iron oxide.